Morphological characterization and assessment of genetic parameters of NERICA mutant rice lines under rainfed condition (Asian Journal of Medical and Biological Research, 2017)
An experiment was conducted to evaluate thirty one NERICA mutant rice genotypes (twenty eight NERICA mutant lines along with three parental lines) of advanced (M4 and M5)generations for morphological characters and genetic parameters assessment in aus season, 2014 at the experimental field of Biotechnology division, BINA, BAU Campus, Mymensingh-2202 following Randomized Complete Block Design (RCBD) with three replications. The genotypes differed significantly for all the traits viz., days to flowering (1st, 50%, 80%), days to maturity, plant height, total tillers and effective tillers hill-1, filled and unfilled grains panicle-1, 100-seed weight (g) and yield plant-1(g).N1/300/P-9-5 had maximum yield plant-1 and N4 parent had minimum yield plant-1. All the parental lines showed less yield compared to other mutant lines. The phenotypic coefficient of variations (PCV) were higher than genotypic co-efficient of variations (GCV) for all the traits studied indicating that they all interacted with the environment to some extent. All the traits studied expressed moderate to high heritability estimates ranging from 43.68 to 92.87%. High heritability along with high genetic advance was noticed for the traits, number of filled grains panicle-1, number of unfilled grains panicle-1 and plant height.Asian J. Med. Biol. Res. December 2016, 2(4): 532-540